2014
DOI: 10.1158/1535-7163.mct-13-1060
|View full text |Cite
|
Sign up to set email alerts
|

Doxycycline as an Inhibitor of the Epithelial-to-Mesenchymal Transition and Vasculogenic Mimicry in Hepatocellular Carcinoma

Abstract: This study was conducted to examine the effects of doxycycline on the survival time and proliferation of hepatocellular carcinoma (HCC) in vivo and on the biologic functions of HCC in vitro. This study was also designed to evaluate the effects of doxycycline on epithelial-to-mesenchymal transition (EMT)-and vasculogenic mimicry (VM)-related protein expression and on matrix metalloproteinase (MMP) and DNA methyltransferase (DNMT) activity in vitro. Human MHCC97H cells were injected into BALB/c mice, which were … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 41 publications
1
43
0
Order By: Relevance
“…Since our studies show that there is Ͼ75% HeLa cell growth inhibition with 4 g/ml of doxycycline treatment, the results seen with the higher doxycycline concentrations (5 and 10 g/ml) used by Meng et al (49) suggest a possible doxycycline-induced toxic effect on hepatic tumor cells. Our RNA-seq data from the parental HeLa cells have further indicated very low expression of cadherins and MMPs and only modestly decreased expression in doxycycline-treated cells (data not shown).…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Since our studies show that there is Ͼ75% HeLa cell growth inhibition with 4 g/ml of doxycycline treatment, the results seen with the higher doxycycline concentrations (5 and 10 g/ml) used by Meng et al (49) suggest a possible doxycycline-induced toxic effect on hepatic tumor cells. Our RNA-seq data from the parental HeLa cells have further indicated very low expression of cadherins and MMPs and only modestly decreased expression in doxycycline-treated cells (data not shown).…”
Section: Discussionsupporting
confidence: 49%
“…Doxycycline treatment has been shown to inhibit hepatic tumor cell growth through inhibition of epithelial-to-mesenchymal transition (EMT) and by enhanced expression of E-cadherin and reduced expression of N-cadherin, vimentin, twist, and snail (49). Since our studies show that there is Ͼ75% HeLa cell growth inhibition with 4 g/ml of doxycycline treatment, the results seen with the higher doxycycline concentrations (5 and 10 g/ml) used by Meng et al (49) suggest a possible doxycycline-induced toxic effect on hepatic tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…These unique tubes are lined by tumor cells able to transfer red blood to the surrounding tumor tissue, simultaneously providing a path for tumor cell metastasis [9,12]. VM was found in 53 of 89 HCC samples (59.6%).…”
Section: Resultsmentioning
confidence: 99%
“…VM is associated with the host blood circulation to provide a blood supply for tumor tissue, which suggests that VM is functional [6]. Early studies in our laboratory showed that VM was found in HCC and that EMT was involved in the formation of VM [7,8,9]. …”
Section: Introductionmentioning
confidence: 99%
“…EX-T9592-Lv201) or a negative control (EX-NEG-Lv201) and lentiviral expression plasmids with Nodal shRNA (HSH011861-HIVU6) or a shRNA control (CSHCTR001-HIVU6) were purchased from GeneCopoeia, Inc. The lentivirus-mediated transfection was performed as described previously [56]. MDA-MB-231 cells were transfected with the Nodal shRNA vector (MDA-MB-231-shNodal) or the shRNA control vector (MDA-MB-231-shCon), and MCF-7 cells were transfected with the Nodal cDNA vector (MCF-7-Nodal) or the control (MCF-7-Con).…”
Section: Methodsmentioning
confidence: 99%